Hernial trauma: Gunshot wound. Intestinal perforation - Castro, María Teresa; Castelli, Fernando; Fígoli, Luis; Folle, Enrique; Belloso, Rogelio (Cirugía del Uruguay, 1997)
The authors present the case of a 20 year old mate carrier of a right inguinal herniary recidive who suffers a bullet injury in right thigh and scrotum.